Experimental characterization of friction and wear behavior of textured Titanium alloy (Ti-6Al-4V) for enhanced tribological performance. (18th August 2021) - Segu, Dawit Zenebe; Wang, Lei-Lei; Hwang, Pyung; Kang, Seok-Won
Abstract: Laser surface texturing (LST) is an effective surface engineering technique that can improve the efficiency and reliability of a tribosystem. In this study, surface textures with combined dimple patterns were prepared on a Ti-6Al-4V alloy surface using a Nd:YAG pulsed laser. Sliding dry and MoS2 solid-lubricated experiments were performed to assess the tribological characteristics of these specimens using a ball-on-disk mode. An L9 (3 4 ) orthogonal array table was used to prepare an experimental plan, which contained three parameters: the sliding speed, applied load, and the area density of dimple on the friction properties. The results show that the MoS2 -added textured surface effectively decreased the coefficient of friction and reduced adhesion wear compared to an untextured surface. Analysis of variance (ANOVA) suggested that the texture area density has a major effect on the friction coefficient at a confidence level of 99%, followed by the applied load and sliding speed. Scanning electron microscopy (SEM) revealed that the wear mechanisms were adhesive and abrasive wear, and a transfer layer from the Ti-6Al-4V alloy was obtained on the counterpart ceramic ball. In conclusion, a higher texture area density is advantageous to increase the friction and wear performance of the Ti-6Al-4V alloy surface.